Maintenance based Bevacizumab versus complete stop or continuous therapy after induction therapy in first line treatment of stage IV colorectal cancer: A meta-analysis of randomized clinical trials. (August 2016) - Tamburini, Emiliano; Rudnas, Britt; Santelmo, Carlotta; Drudi, Fabrizio; Gianni, Lorenzo; Nicoletti, Stefania V.L.; Ridolfi, Claudio; Tassinari, Davide
Abstract: Background: In stage IV colorectal cancer, bevacizumab-based maintenance therapy, complete stop therapy and continuous therapy are considered all possible approaches after first line induction chemotherapy. However, there are no clear data about which approach is preferable. Material and methods: All randomized phase III trials comparing bevacizumab-based maintenance therapy (MB) with complete stop therapy (ST) or with continuous therapy (CT) were considered eligible and included into the analysis. Primary endpoint was the Time to failure strategies (TFS). Secondary endpoints were Overall Survival (OS) and Progression free survival (PFS). Meta-analysis was performed in line with the PRISMA statement. Results: 1892 patients of five trials were included into the analysis. A significant improvement in TFS (HR 0.79; CI 95% 0.7–0.9 p = 0.0005) and PFS (HR 0.56; CI 95% 0.44–0.71 p < 0.00001) were observed in favour of MB versus ST. A trend, but not statistically significant, in favour of MB versus ST was also observed for OS (HR 0.88; CI 95% 0.77–1.01, p = 0.08). Comparing maintenance therapy versus continuous therapy no statistically differences were observed in the outcomes evaluated (OS 12 months OR 1.1 p = 0.62, OS 24 months OR 1 p = 1, OS 36 months OR 0.54 p = 0.3, TFS 12 months OR 0.76 p = 0.65). Conclusions: Our meta-analysis suggests that use of MB approach increases TFS, PFS compared to ST. Although without observing any statistically advantage, it should be highlighted that MB versus ST showed a trend in favour of MB. We observed no difference between MB and CT. MB should be considered the standard regimen in patients with stage IV colorectal cancer after first line induction therapy.